A novel route to produce structural polymer foams with a controlled solid skin-porous core structure based on gas diffusion mechanisms. (March 2020) - Pinto, J; Escudero, J; Solórzano, E; Rodriguez-Perez, MA
A comprehensive study about a new production route of structural polymer foams is presented. This methodology is based on the one hand on a free foaming process induced by a chemical blowing agent inside a closed mold, and on the other hand on the use of a solid polymer able to absorb gas in close contact with the molten foamed polymer, establishing a competitive absorption of the blowing gas between both materials. This competitive absorption of the gas promotes the formation of a solid skin in all the areas in contact with the solid polymer. This phenomenon has been identified in-situ and evaluated in real time using a specific X-ray radioscopy set-up, being possible to relate unequivocally the apparition and thickness of the solid skin with the presence of the solid polymer and with the pressure achieved in the closed mould during the foaming process. The presented production route shows an accurate and independent control of the final foam relative density (even below 0.5) and the thickness of the solid skin, together with an excellent surface quality and a broad applicability, which allows the design and production of structural polymer foams with exceptional features.